Damage mechanisms in hybrid composites: experimental characterisation and energy-based numerical analysis (Fracture and Structural Integrity, 2025)
This study analyses the failure mechanisms of bilayer hybrid composites, consisting of carbon and glass fibres embedded in an epoxy matrix, under bending loads. The objective is to evaluate how different hybrid configurations influence failure evolution and mechanical performance. To achieve this, specimens are submitted to 3-point bending tests, and 3D finite element models are developed to simulate the experimental setup. The numerical models incorporate a continuum damage mechanics model to capture intralaminar failure and a surface-based cohesive behaviour for interlaminar damage. The results show that hybrid laminates exhibit intermediate strength and displacement values compared to nonhybrid carbon and glass laminates, with the positioning of glass fibers significantly affecting bending force and displacement. Intralaminar damage is the primary failure mechanism in all configurations, followed by delamination. Additionally, placing glass fibers on the compression side reduces the overall damage, whereas placing them on the tensile side increases intralaminar failure before reaching the peak load. These findings contribute to optimizing the design of hybrid composites for bending applications by providing information about the relationship between material configuration and failure mechanisms, ultimately improving their structural efficiency and durability in engineering applications.
Keywords: Fiber’s hybridisation; epoxy composites; damage mechanisms; bending behaviour; numerical analysis